Preparation and spectroscopic investigation of newly schiff Base of 5-chloro-2-hydroxybenzylidene)-3,4,5-trihydroxybenzohydrazone with some metal ions - Alhadi, A.A.; Mahmood, A.A.; Ali, Hapipah Mohd; Yehye, W.A.; Shaker, S.A. (2011)
An ethanolic solution of metal salts was added slowly to an ethanolic solution of 5-chloro-2hydroxybenzylidene)-3,4,5-trihydroxybenzohydrazone with few drops of Methylamin to give complexes with the general formula [M(GHL2) 2]. 2H 2O, [Cu 2(GHL2) 2]. 4H 2O and [Cd(GHL2)(CH 3COO) 2]. 2H 2O where M is Ni(II) and Zn(II), GHL2 is 5-chloro-2-hydroxybenzylidene)-3,4,5- trihydroxybenzohydrazone. The resulting complexes were characterized by elemental analysis, magnetic measurements and spectral studies. The Schiff base GHL2 ligand acts as tridentate ligand was coordinated with the metal ions through O, N, O except with Cd(II) as the ligand behaves as bidentate ligand coordinated with Cd(II) ion through O, N atoms. However, [M(GHL2) 2J. 2H 2O and [Cd(GHL2)(CH,COO) 2]. 2H 2O were proposed to possess Octahedral geometry while [Cu 2(GHL2) 2]. 4H 2O was proposed to possess tetrahedral geometry.